Strategy for Implementing the Recommendations of the Republic of Indonesia Audit Board on Financial Reports of the Regional Government of South Buton Regency - Hasiba Ilsa; Muhammad Toaha; Retno Fitriani (Journal of Social and Humanities, 2023)
South Buton Regency has great economic potential but faces various challenges in managing government finances. Local government financial reports are a very important tool in decision-making, monitoring, and accountability to the community. The purpose of this study is to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, and then formulate a priority strategy for implementing BPK RI recommendations in the financial reports of the regional government of South Buton Regency. Primary data is used through field observations and interviews, while secondary data is obtained from previous research, books, and related agencies. The results of the study indicate alternative strategies that can be considered, including increasing transparency and effective cooperation with BPK RI, competency development and openness to organizational changes, strong local government commitment in dealing with legal threats, and transparency as protection from reputation threats and changes in priorities in economic conditions uncertainty and overcoming resistance within local government.